PENGEMBANGAN EKOWISATA TELUK WANG DAN KINERJA PEMERINTAH DESA BIUKU TANJUNG, KABUPATEN MERANGIN, PROVINSI JAMBI - Sarinah; Mardalena; Athika; Maharani; Cindy Kartika Saputri; Sella Suwarni; Ana Fizka; Maheri Saputra; Muhammad Fazriel (Hira Institute, 2026)
Teluk Wang is a natural tourism area in Biuku Tanjung Village, Merangin Regency, Jambi Province. This area has good natural potential to be developed as a community-based ecotourism destination. However, the tourism area has not been managed well due to limited facilities, poor access, and the absence of clear tourism management. This community service activity aims to identify tourism potential, understand existing problems, and prepare simple development strategies that focus on environmental sustainability and community involvement. The method used was a participatory qualitative approach through field observation, interviews with local residents and village officials, and documentation. The results show that Teluk Wang has attractive natural scenery but still needs improvements in basic facilities, human resource capacity, and tourism management to support local economic activities while protecting the natural environment.